An Orientalist Today: Jonathan A.C. Brown's Thoughts on Hadith - Nur Hamidah Pulungan (Ulumuna, 2023)
The term "Orientalist" refers to scholars, mostly from the West, who specialize in studying Eastern cultures, including Islamic texts such as the Quran and Hadith. This study explores the views of a contemporary Orientalist, namely Jonathan Andrew Cleveland Brown, on Hadith. Grounding on Brown's works on hadith and related topics as the main data, this study found that Brown has introduced a distinctive concept known as “the canonization theory”, typically applied as a stage in the cult or development of the Bible and Torah. Brown has applied the theory to explore the history of the books of hadith composed by Bukhari and Muslim. His perspective ultimately supports the consensus of Muslim scholars who consider Sahih Bukhari and Muslim as the primary source of Islamic law after the Quran. The canonization of Sahihain has undergone extensive study and critique from hadith experts. The reception of Sahih Bukhari has also experienced dynamics, such as the rejection by the Naisabur community, who favored Sahih Muslim, until Sahih Bukhari was established as the foremost reference on hadith, inspiring the development of a new epistemology in the study of hadith. Overall, Brown advocates for a balanced approach to Hadith, respecting Islamic tradition while maintaining a critical and scientific perspective in understanding and interpreting hadith.